1994
DOI: 10.1017/s0007485300032193
|View full text |Cite
|
Sign up to set email alerts
|

The development of suppression tactics for Biprorulus bibax (Heteroptera: Pentatomidae) as Part of an integrated pest management programme in citrus in inland South-eastern Australia

Abstract: Suppression tactics for the citrus stink bug pest, Biprorulus bibax Breddin, were developed and implemented during 1987-1992 in four lemon orchards in southern New South Wales, Australia. Tactics were based on introduction and conservation of natural enemies (principally egg parasitoids), physical or chemical treatment of overwintering populations and strategic low rate applications of a selective insecticide. Estimated adult populations of 10-35,000/1.5 ha and 70-90% fruit damage in untreated crops were reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…staining/drying of fruit and fruit drop (Hely et al, 1982;James, 1994). Recent research on the biology and ecology of this native insect (e.g., James, 1990aJames, -c, 1991James et al, 1990) led to development and adoption of an integrated management strategy based on monitoring, natural enemy conservation, and judicious use of the insecticide, endosulfan, at a rate harmless to natural enemy survival (James, 1993(James, , 1994. However, endosulfan is likely to be removed from use as a horticultural pesticide in Australia in the near future and an alternative control tactic is required.…”
Section: Introductionmentioning
confidence: 99%
“…staining/drying of fruit and fruit drop (Hely et al, 1982;James, 1994). Recent research on the biology and ecology of this native insect (e.g., James, 1990aJames, -c, 1991James et al, 1990) led to development and adoption of an integrated management strategy based on monitoring, natural enemy conservation, and judicious use of the insecticide, endosulfan, at a rate harmless to natural enemy survival (James, 1993(James, , 1994. However, endosulfan is likely to be removed from use as a horticultural pesticide in Australia in the near future and an alternative control tactic is required.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that halving the application rate of imidacloprid did not reduce its efficacy against SCB. It is possible that the rate can be reduced further without compromising the control efficiency, as has been demonstrated for the control of SCB with endosulfan (James, 1993(James, , 1994. Long-term solutions to the withdrawal of endosulfan, however, will require more selective insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, control of SCB relies heavily on the judicious use of endosulfan, an organochlorine compound. When used at a very low rate (10-15 mL/100 L), endosulfan is very effective against SCB but is harmless to most other invertebrates found in citrus groves, including the natural enemies of SCB and other citrus pests (James, 1994). Unfortunately, it is inevitable that endosulfan will eventually be removed from use in citrus, as is the case in most other countries.…”
mentioning
confidence: 99%
“…Inundative release of egg parasitoids has successfully been employed for control of pentatomid bugs on various crops (James 1993; Correa‐Ferreira & Moscardi 1996). Background parasitisation levels for P. affinis are clearly insufficient to control the pest, and releases of additional T. basalis or Telenomus sp.…”
Section: Discussionmentioning
confidence: 99%